Le rôle de la philosophie de l'éducation dans la formation des maîtres - Gohier, Christiane (Paideusis, 1990)
We cannot talk about the role of philosophy of education in teachers' training programs without examining the relationship between philosophy and educational theories. Even when theoreticians like Kieran Egan, for example, claim that education is a normative discourse that cannot be inferred from "local" empirical psychological research, the role of philosophy seems of utmost importance because philosophy has essentially to do with norms and values. Another way of looking at the "sciences" of education that renews our comprehension of their relationship is by analysing a new cognitive psychological approach named "metacognition" which rests on one's ability to understand one's own cognitive strategies and mechanisms of regulation. The well-known psychologist Adrien Pinard in Quebec has been working on those concepts lately, inspired by Flavell's model of cognitive regulation. This approach is remarkably similar both to Wilson's definition of procedural criteria which he claims educational theory is all about and to the very specific method of philosophy, that of analytical and reflective thought. Philosophy or reflective thought cannot be separated from practice in teacher training since education is not only a matter of pedagogical means but also of attitudes to and relationship with another person. Thus, besides theory and practice, a third parameter should be taken into account in the elaboration of a teacher training program: the meta-practice and theory parameter, or the reflection on one's own practice, which is essentially philosophical.